COMPLEMENTARY AND ALTERNATIVE MEDICINE USERS IN SERBIA HEALTH SELF-EVALUATION: CROSS-SECTIONAL NATIONAL STUDY - Luketina-Šunjka, Marina; Rančić, Nemanja; Mihailović, Nataša; Radević, Svetlana; Dragović, Saša; Jakovljević, Mihajlo (Acta medicae Medianae, 2021)
The aim of the research was to examine the influence of the respondents’ health status on the use of complementary and alternative medicine methods. This was a population-based, cross-sectional study. The sample consisted of 550 interviewed persons, from the third National health survey of the residents of Serbia in 2013, who had used complementary and alternative medicine (CAM) services in the preceding 12 months. Just over 2/3 of CAM users have chronic health disorders (p<0.01), the most commonly diagnosed chronic health disorder among CAM users was hypertension (36.7%). Every seventh and partially every fourth CAM user has been seriously restricted as regards undertaking normal daily activities for the last 6 months or longer. CAM users are more satisfied with the services they receive in private practice (p<0.01). The two out of three users of CAM services rate their health as good and/or average. CAM users are more satisfied with the services they receive in private practice, the highest percentage of them rated their health as good. The analysis of the impact of respondents’ health status, the analysis of the correlation between the respondents’ self-health assessment and the use of alternative medicine methods, analysis of the impact of socio-demographic characteristics on the use of CAM, along with a comparative analysis of the use of health care services – would significantly contribute to better recognition of CAM by the Ministry of Health.